Detailed Survey on Phishing and Anti-Phishing Techniques - Bhowmick, Anirban (International Journal of Computer Sciences and Engineering, 2015)
Internet has been a pathway for cybercrimes. The facility internet has delivered is vast but at the same time data privacy of individuals has been risked. Phishing is an example of social engineering techniques used to deceive users. In this paper, the authors made an attempt to enlighten readers with the different aspects of phishing. Public awareness is essential to combat such crimes. Different types of phishing techniques, their avoidance and detection has been presented in this paper. Further, a section highlights numerous research works on anti-phishing techniques. The later part of the paper illustrates the phishing scams and statistics for greater understandability of the problem. The readers are also informed about the various anti-phishing groups and where to report any sort of suspicious phishing activity.